Hydroxyethyl starch-curcumin nanoparticles ameliorate DSS-induced ulcerative colitis in mice via synergistic TLR4/NF-κB suppression, Nrf2 activation, intestinal barrier restoration, and gut microbiota modulation - Li, Sheng; Lu, Shiyi; Xiong, Jiahui; Chen, Liang; Lin, Yanting; Chen, Xiaohui; Wang, Xinyi; Lin, Lijing; Cai, Xiaoliang; Yang, Xiaoyu (Frontiers in Pharmacology, 2025)
Here, we systematically evaluated the therapeutic efficacy and mechanisms of action of in-house synthesized hydroxyethyl starch-curcumin nanoparticles (HES-CUR NPs) in ulcerative colitis (UC). Using a dextran sodium sulfate (DSS)-induced UC mouse model, we analyzed the effect of HES-CUR NPs on colonic tissue and the gut microbiota through the assessment of organ indices and serum biochemical markers, histopathology, immunohistochemistry, Western blot, and 16S rRNA sequencing. We found that HES-CUR NPs significantly suppressed the TLR4/NF-κB inflammatory pathway (downregulated TLR4, p-IKKβ, IL-1β, IL-6, NFKB, MyD88, and p-IKKB/IKKB; p < 0.01), activated the Nrf2/HO-1 antioxidant pathway (enhanced Nrf2 nuclear translocation and HO-1 expression), and upregulated the expression of tight junction proteins (claudin-1, occludin, ZO-1), thereby restoring intestinal barrier integrity. Microbiota analysis revealed that HES-CUR NPs increased gut microbiota diversity (elevated Chao1, Shannon, and ACE indices) and enriched beneficial bacteria abundance (Ligilactobacillus murinus, Lactobacillus johnsonii). Antibiotic intervention partially attenuated the therapeutic effects of the HES-CUR NPs, confirming that their effects involved microbiota-dependent mechanisms. Compared to CUR and SASP, HES-CUR NPs exhibited significantly enhanced bioavailability and efficacy (p < 0.01), attributed to the targeted delivery and sustained-release properties of the hydroxyethyl starch nanocarrier. No toxicity was observed, as indicated by normal spleen, liver, and thymus indices and stable levels of TP, ALT, AST, ALB, GLB, and ALB/GLB. Our findings indicated that HES-CUR alleviates UC through a synergistic, multi-target mechanism involving inflammatory pathway suppression, antioxidant pathway activation, intestinal barrier repair, and microbiota modulation, providing a theoretical foundation for developing efficient and safe natural nanomedicines targeting UC.